Modelado de un Sistema de Acceso Múltiple por división de código en el Entorno Óptico - Amaya Ocampo, Waldimar Alexander; Gómez Paredes, Juan Carlos (Ingeniería, 2005)
This paper describes the OCDMA technology (Optical Code Division Multiple Access) focussing on the coherent systems OCDMA. The modelling was done using VPI v7.0 and the results of the simulations are presented. The utility of OCDMA as a control access technology it's demonstrated by the simulations which describe the most important aspect to be considered to evaluate the performance of coherent OCDMA Systems.